Analisis Kebutuhan Siswa Kelas XII di SMKN 1 Susut Terhadap Media Pembelajaran Berbasis Android Pada Mata Pelajaran Bahasa Inggris - I Nyoman Sudirman; Ni Wayan Karti; Ni Made Budiasih (Peneliti.net, 2022)
This research was conducted with the aim of being able to find out students' needs for android-based learning media in English subjects. This study used quantitative methods, with the subject of class XII Hospitality A students at SMK N 1 Susut. The process of collecting data in this study was carried out by means of observation, interviews, and giving questionnaires to students consisting of 28 students. The answer results from the questionnaire were then processed in the form of a percentage in the form of a table and agaram. The results of the analysis of students' needs for android-based learning media show that students really need the media, and students are also very interested in using android-based learning media in the English learning process, this is evidenced by the response to the questionnaire given to students, namely 96.4% of students agreed that in the English learning process using android-based learning media.